1973
DOI: 10.1017/s0024282973000447
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Ontogeny of Fruiting Bodies in the Genus Cladonia and their Taxonomic and Phylogenetic Significance

Abstract: FIG. 1A, Schematic drawing of ontogenetic type I. Ascogonia are formed on the level of the thallus horizontalis and the ascogenous hyphae grow upwards with the podetium (Aascogonium; Ap-apothecium; gT-generative tissue; Po-podetium; T-trichogyne). B, Schematic drawing of ontogenetic type II. Ascogonia are formed at the top of the mature podetium (Al-algae; Ap-apothecium; gT-generative tissue; Po-podetium; Poyyoung podetium, T-trichogyne). C, Schematic drawing of the ontogenetic type III. No podetium is formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1974
1974
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 2 publications
0
16
0
1
Order By: Relevance
“…For example, Gymnoderma has an entirely amyloid ascus tip structure (Per soh et al, 2004), so delimiting characteristics remain to be discovered. Conversely, the ontogeny of the ascomata has been studied in detail in most genera of Cladoniaceae (Jahns, 1970a;Jahns and Beltman, 1973;Hammer, 1993;Jahns et al, 1995;Grube and Hawksworth, 2007), although the interpretation of some structures has been controversial (Hammer, 1993(Hammer, , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gymnoderma has an entirely amyloid ascus tip structure (Per soh et al, 2004), so delimiting characteristics remain to be discovered. Conversely, the ontogeny of the ascomata has been studied in detail in most genera of Cladoniaceae (Jahns, 1970a;Jahns and Beltman, 1973;Hammer, 1993;Jahns et al, 1995;Grube and Hawksworth, 2007), although the interpretation of some structures has been controversial (Hammer, 1993(Hammer, , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ahti (1961) estimated that in continuous ground cover of Cladina on average at least one fertile podetium is likely to occur per square metre. However, on these infrequent fertile podetia there is often synchronous development of abundant (frequently >100) apothecia (Jahns and Beltman, 1973;Jahns and Ott, 1997;Jahns et al, 2004) each developing at a branch tip. Prior to the development of apothecia, aerial hyphae, believed to be trichogynes, develop at branch endings (Honegger, 1984;Jahns and Beltman, 1973;Jahns et al, 2004) and have been observed with conidia (putative spermatia) attached (Honegger, 1984).…”
Section: Breeding Systems In Lichen-forming Fungimentioning
confidence: 99%
“…Moreover, these podetia seem to grow from primary squamules that do not have the yellow lower surface characteristic of C. luteoalba, but greatly resemble the squamules of, for instance, C. borealis or C. coccifera. The other (escyphose) podetial type very clearly grows from primary squamules which have the yellow lower surface, and young developmental stages of podetia were also observed (their ontogeny following types I or IV of Jahns & Beltman 1973).…”
Section: Morphologymentioning
confidence: 99%